INCREASING THE SOFT SKILLS AND HARD SKILLS OF STUDENT OUTSTANDING YOUTH THROUGH TECHNOPRENEURSHIP TRAINING IN NORTH KONAWE DISTRICT - Asrip Putera; Rostin Rostin; Endro Sukotjo; Isalman Isalman (International Journal of Engagement and Empowerment, 2022)
Unemployment is one of the fundamental problems in the economy, various programs from the government are directed at reducing unemployment, such as; training, venture capital assistance, and so forth. These programs have had quite an encouraging impact, but there are still spaces that need to be filled in order to further maximize existing government programs. One community group that needs to be strengthened in terms of soft skills and hard skills is youth who have dropped out of school. Providing skills and other abilities for out-of-school youth will foster self-confidence and work ability so that they are able to be more independent and even create jobs for other youth. Some of the problems faced by out-of-school youth, especially in Sambandete Village, Oheo District, North Konawe Regency are; First, lack of creativity, Second, lack of skills and third, lack of self-confidence so that most of the youth who drop out of school become unemployed so that it becomes a burden on the family. The resulting activity achievement is the increase in the soft skills and hard skills of school dropout youth. The targets that have been achieved in this activity are: (1). Increasing the creativity of dropout youth, giving birth to creative ideas for business. (2). Increasing the self-confidence of dropout youth in socializing so that they are able to socialize and develop networking. (3). Increasing the business skills of out-of-school youth as a provision to build a business. The tecnopreneurship training contains materials that provide the ability to increase creativity, self-confidence and improve skills. The enthusiasm of the participants in attending the training was relatively good, this can be seen from the number of invitations distributed to the number of people who attended. The number of invitations distributed was 30 invitations and 30 people attended, so it can be concluded that the level of community attendance in the training reached 100 percent. Besides the relatively high level of attendance, community participation can also be seen from the activeness of the training participants in giving opinions, comments and questions about the material presented. Some participants asked more than once, this was because the participants wanted to know more about the content of the material presented, they even asked the moderator to open several question sessions so that in this activity it was planned to open two question and answer sessions into four sessions